Strengths Model-Based Nursing Interventions for Inpatients in Psychiatric Inpatient Settings Using a Seclusion Room: A Case Series Study - Yutaka Nagayama; Koji Tanaka; Masato Oe (MDPI AG, 2023)
The use of coercive measures in psychiatric inpatient settings has been an important issue for many years. Nursing interventions based on a strengths model could enable a reduction in the use of these measures. This study aimed to describe the practice of nursing interventions using a strengths model for psychiatric inpatients who have been in seclusion for a long time. We also constructed a nursing model to minimize coercive measures. The participants were eight inpatients who had been in seclusion for a long time. Nursing interventions based on a strengths model were implemented in collaboration with nurses from six long-term care units in three psychiatric hospitals in Japan. For 4 of the 8 participants, the seclusion time decreased by 20-45%. However, for another 2, it increased by about 23-34%. An average decrease of 9.6% was observed, and the open observation time increased by 1.4 h per day on the seclusion days. When using this model, the nurses considered the effects of stimulating strengths. We believe this approach may promote inpatients' self-insight. Considering the perspective of stimulus adjustment might be useful for maximizing the positive effects of working on strengths.